In the name of the father, reason and the revolution: a reading of the economy of sexual difference in the Chilean revolutionary telos - Montalva, Joaquín (2021)
The following thesis consists of a close reading of the main working-class periodicals published in Santiago (Chile) between 1870s and 1920s. The aim of this work is to analyse and reconstruct the inner logic of the arguments that the Chilean urban workers developed for interpreting the origin of Capitalism, the state of exploitation, the effects of the labour routine on their bodies and minds, and the means for the revolution from a deconstructive and feminist perspective. In other words, it consists of a critical exercise of systematization of this material in order to explore the ways in which these workers re-wrote Marxist, Anarchist and Socialist theories according to their conditions and locality from a critical perspective.